IMPLEMENTASI FUZZY ANALYTICAL HIERARCHY PROCESS DALAM PEMILIHAN SUPPLIER SERTA ALOKASI PESANAN BERAS MENGGUNAKAN METODE GOAL PROGRAMMING - Nasution, Achmad Suryadi; Aprilyani, Erika; Mardianto, Lutfi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2025)
In the face of current business competition, existing companies are competing with each other to get optimal output in order to compete with other companies. One of the steps that can be taken to be able to obtain optimal output is to choose potential suppliers in obtaining profits. This research uses the fuzzy analytical hierachy process method with the aim of knowing the priority of suppliers who will cooperate and also the goal programming method with the aim of determining the allocation of rice orders in order to minimize purchase costs, minimize the percentage of defects, maximize supplier weight and meet supply targets. The results of supplier 1, supplier 2, and supplier 3 weights are 0.3145; 0.3489; 0.3365 respectively. The goal programming method provides a better solution than the current order allocation. The total purchase cost set by the company did not decrease or increase but the total defective orders decreased by 23.43% in one year.